Investigation of Wear and Friction Behavior of Cobalt-Chromium-Molybdenum Alloy Produced by Laser Powder Bed Fusion - Ramezani, Maziar; Ripin, Zaidi Mohd (MDPI AG, 2023)
This study investigates the sliding wear resistance of the Co-28Cr-6Mo alloy manufactured by laser-based powder bed fusion through linear reciprocating sliding wear tests. Varied loads and sliding speeds, in both dry and lubricated contact scenarios, were examined using a hardened steel ball as a counter material. Microhardness profiles were obtained to understand the alloy’s mechanical behavior, revealing consistent average microhardness values of 409.67 HV through the thickness and 404.05 HV along the wear track. The coefficient of friction (COF) indicated a decrease in COF with an increase in the applied normal load in both dry and lubricated contacts. On the other hand, the COF increased with higher sliding speeds, and remained stable under lubricated contact but fluctuated in dry conditions over time. Increased applied load and sliding speed correlated with escalated wear rates. Investigation of the impact of different lubricants on tribological properties highlighted synthetic gear oil as the most effective in reducing wear rate among tested lubricants. Wear mechanisms were elucidated through scanning electron microscopy and energy-dispersive X-ray spectroscopy. The presented results can serve as a guide for selecting suitable operating conditions and lubricants to reduce wear in Co-Cr-Mo alloy applications.
Keywords: 4014 Manufacturing Engineering; 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; 4017 Mechanical Engineering